1981
DOI: 10.1002/sce.3730650503
|View full text |Cite
|
Sign up to set email alerts
|

Inquiry‐Related Tasks in High School Science Laboratory Handbooks

Abstract: While early approaches to curriculum evaluation focused upon student cognitive growth as the primary criterion of success or failure, more recently educators have recognized the importance of a number of other criteria. What are the effects of the curriculum upon student attitude, cognitive preference, and intellectual development? What are the effects of the curriculum upon the development of problem-solving skills and upon interpersonal communication skills? Some researchers now examine classroom transaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
5

Year Published

1983
1983
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(48 citation statements)
references
References 3 publications
2
41
0
5
Order By: Relevance
“…The inquiry levels in the physics practical examinations were restricted to structured and confirmation inquiry levels, with the former dominating. To a large extent the findings in this study are similar to those reported in previous studies that examined science textbooks and laboratory manuals (Tamir & Luneta, 1981;Staver & Bay, 1987;Pizzin, Shepardson, & Abell, 1991) and laboratory manuals (Friedler & Tamir, 1986;Germann, Haskins & Auls, 1996;Staer, Goodrum & Hackling, 1998). However, there is some consistency in the coverage of inquiry skills in the syllabus and practical examinations.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The inquiry levels in the physics practical examinations were restricted to structured and confirmation inquiry levels, with the former dominating. To a large extent the findings in this study are similar to those reported in previous studies that examined science textbooks and laboratory manuals (Tamir & Luneta, 1981;Staver & Bay, 1987;Pizzin, Shepardson, & Abell, 1991) and laboratory manuals (Friedler & Tamir, 1986;Germann, Haskins & Auls, 1996;Staer, Goodrum & Hackling, 1998). However, there is some consistency in the coverage of inquiry skills in the syllabus and practical examinations.…”
Section: Conclusion and Discussionsupporting
confidence: 88%
“…For example, in Israel, Tamir and Luneta (1981) analyzed high school science textbooks and found that the activities in the textbooks lacked opportunities for students to investigate and inquire. In another study of curriculum materials used in Israel, Friedler and Tamir (1986) analyzed high school science laboratory manuals and classroom observations and found that most activities were at lower levels of inquiry.…”
Section: Definitions and Previous Research On Inquirymentioning
confidence: 99%
See 2 more Smart Citations
“…Except observation, it was an effective method to refer to students' routine. In addition, Krajcik, Czerniak & Berger thought that achievement of Science Project inquiry could demonstrate students' leanings; it could be used for assessment [28]- [30].…”
Section: Introductionmentioning
confidence: 99%